Monkey see, monkey do: Truth-telling in matching algorithms and the manipulation of others - Pablo Guillen; Rustamdjan Hakimov (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
We test the effect of the amount of information on the strategies played by others in the theoretically strategy-proof Top Trading Cycles (TTC) mechanism. We find that providing limited information on the strategies played by others has a negative and significant effect in truth-telling rates relative to full or no information about others' strategies. Subjects report truthfully more often when either full information or no information on the strategies played by others is available. Our results have potentially important implications for the design of markets based on strategy-proof matching algorithms.
Keywords: C78; D79; D80; I20; 330; school choice; top trading cycles; strategy-proofness